Possible relationships of selected food items to osteoporosis among a group of Iraqi women - saleh, may fawzi; aldiwan, jawad; Ahmed , Ammar H. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Osteoporosis is a global health problem which is estimated to affect more than 200 million people worldwide, especially postmenopausal women. It is characterized by decreased bone mineral density leading to fragility and increased risk of fractures.  Objective: This study was conducted to explore the consumption of inappropriate foods related to osteoporosis among a group of Iraqi women.Patients and methods: A cross sectional study of 140 females aged ≥ 40 years attending polyclinics in Al-Dora sector in Baghdad city from 18th January to 24th April 2021. The bone mineral density was measured by portable quantitative calcaneal ultrasound machine (osteosystem) and the bone was assessed for osteoporosis by T-score. Food frequency questionnaire was used for collecting data related to food consumption. Results: Out of the total sample, 74 (52.9%) were found to be osteoporotic. There was a significant association with high salt and coffee consumption with the occurrence of osteoporosis (77.3% and 83.3%, respectively, p = 0.001), compared to those who did not consume caffeinated drinks. Participants with daily consumption of caffeinated drinks had a highly significant association with osteoporosis (21.8% vs 100%, p = 0.001).Conclusion: Excessive consumption of salty foods and caffeinated beverages appears to exert a negative effect on bone mineral density and the occurrence of osteoporosis among the studied group of Iraqi women.